Penerapan Metode Linier Programming untuk Membuat Perencanaan Produksi yang Optimal - Ayudina Puji E, Bagus Asmono (Jurnal Teknik Industri, 2000)
Alocation problem of sources among the chalbanged activities will appear when company have to some activities that have limited resources to do it like PT. Berlina Plastics Pandaan face limited time machine for their each activity makes under time and over time on it. This make unexpected production cost caused subjective production planning that have been done based on the last experience.